The Surrender of Fugitive Offenders between Mainland China and Hong Kong: European Arrest Warrant Model or US Interstate Rendition Model? - Yin, Yanhong (Utrecht Journal of International and European Law, 2022)
Under the ‘one country, two systems’ policy, the surrender of fugitive offenders between Mainland China and Hong Kong has been debated. This article will frame the debate on the application of traditional extradition rules in Mainland China and Hong Kong by exploring the more recent ‘European Arrest Warrant’ system and the long-standing US interstate rendition system. It thus aims to find a suitable model for Mainland China and Hong Kong. The US interstate rendition system is one domestic system, which seems most appropriate for application to Mainland China and Hong Kong as two regions of the same country. However, this article finds that the US interstate rendition system is too direct and inflexible to be enacted by Mainland China and Hong Kong where the legal situation is more complicated and human rights protection differs. This article argues that the European Arrest Warrant can better address the ‘one country, two systems’ situation of Mainland China and Hong Kong. Mainland China and Hong Kong can learn from the European Arrest Warrant to apply the ‘mutual recognition principle’ and other concrete extradition principles to their own surrender system.